Evaluasi Penerapan Smart Mobility di Jakarta - Sifa Novwidia Agni; Manzila Izniardi Djomiy; Roki Fernando; Catur Apriono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2021)
Urban problems such as congestion caused by the very rapid population growth and high urbanization flows are common problems in big cities like Jakarta. The concept of smart city has developed and started to be implemented in several big cities in Indonesia, including Jakarta. One part of the concept of smart city is smart mobility, which is currently developing to solve various urban problems, especially in public transportation to improve the quality of services that are effective and efficient. This study discusses solutions for implementing the concept of smart mobility in Jakarta based on the level of readiness of each indicator according to the indicators found on the Boyd Cohen Smart City Wheel. The purpose of this study is to provide an overview of the level of readiness for implementing smart mobility in Jakarta and the improvements that need to be made. This study used the literature study method to get an initial picture of conditions in Jakarta, then the assessment used survey data assessment and descriptive qualitative analysis. The results show that basically Jakarta can be said to be ready to implement smart mobility, however, there needs to be improvements and procurement in several aspects of smart mobility.